The role of strategic planning in dealing with educational crises facing government school principals in Jerash Governorate - Ahmad, Majdi Ahmad Mohammad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the role of strategic planning in dealing with educational crises facing government school principals in Jerash Governorate. The researcher used the descriptive survey method, and the tool consisted of a questionnaire consisting of (24) items, which were distributed to a group of principals of public schools affiliated to the Directorate of Education Jerash, which numbered (80) principals, were chosen by a simple random method, and one of the most important findings of the study is that the role of strategic planning in dealing with educational crises facing government school principals in Jerash governorate was given a total average of (3. 23 out of 5), i. e. a degree of approval. (medium), and there were no statistically significant differences between the arithmetic averages of the responses of the sample members on the scale of the role of strategic planning in dealing with educational crises facing government school principals in Jerash governorate due to the variables (gender, years of experience). The researcher recommends the necessity of holding continuous training courses for school principals to encourage them to use strategic planning, and to work to involve all school workers in strategic planning, because of this role in understanding all dimensions and conditions of the work environment in the school.